2011
DOI: 10.1111/j.1365-294x.2010.04944.x
|View full text |Cite
|
Sign up to set email alerts
|

Why replication is important in landscape genetics: American black bear in the Rocky Mountains

Abstract: We investigated how landscape features influence gene flow of black bears by testing the relative support for 36 alternative landscape resistance hypotheses, including isolation by distance (IBD) in each of 12 study areas in the north central U.S. Rocky Mountains. The study areas all contained the same basic elements, but differed in extent of forest fragmentation, altitude, variation in elevation and road coverage. In all but one of the study areas, isolation by landscape resistance was more supported than IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
150
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 60 publications
8
150
1
Order By: Relevance
“…This example illustrates an important and well-known limitation in landscape genetic analyses: features that influence gene flow, but are not highly variable within the landscape, are often not supported in landscape resistance models [77]. This limitation may also explain why we failed to detect an effect of some landscape variables that are known to strongly influence movement behavior of bighorn sheep (e.g., forested areas, anthropogenic development).…”
Section: Discussionmentioning
confidence: 92%
“…This example illustrates an important and well-known limitation in landscape genetic analyses: features that influence gene flow, but are not highly variable within the landscape, are often not supported in landscape resistance models [77]. This limitation may also explain why we failed to detect an effect of some landscape variables that are known to strongly influence movement behavior of bighorn sheep (e.g., forested areas, anthropogenic development).…”
Section: Discussionmentioning
confidence: 92%
“…However, our results suggest roads do not unduly influence functional connectivity. Indeed, while previous landscape genetic studies have found roads as a limiting factor to gene flow in black bears, the relative influence of roads varies among populations (Cushman et al., 2006; Short Bull et al., 2011), and in some cases, roads may serve to facilitate rather than impede bear movement (Balkenhol & Waits, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Short Bull et al. (2011) found higher correlations between land cover and black bear gene flow in landscapes where forest cover was highly fragmented compared to landscapes of contiguous forest. Yet, the absence of a landscape effect on 2002 SGS may reflect a time lag between when landscape change occurs and when SGS response to landscape change becomes evident (Anderson et al., 2010; Epps & Keyghobadi, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such movements crossing urban areas may be attributed to a lack of resources, such as food and water in their usual suitable habitat (Sierra Corona et al 2005). Previous results suggest that landscape may play an important role in establishing the population structure of the black bear in its distributional range (Short Bull et al 2011). Our population comparisons among localities of Nuevo León suggested low levels of genetic differentiation, especially between localities which are separated by only a few kilometers, such as Real de Minas Viejas and Picachos, situated on the flanks of the mountains with no notable geographical barrier between them.…”
Section: Discussionmentioning
confidence: 99%